Frank Alden Hill genealogical collection - Hill, Frank Alden
Legal records, genealogical records, pedigree charts, and heraldic crests relating to the Chase, Hathaway, Hill, Lawrence, Stephens (Stevens), and Townley families. Records relate to inhabitants of New Jersey, New York, Maryland, and Virginia.
Handwritten copies produced from originals in American and European library and museum collections.
Lawyer and genealogist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Chase family; Hathaway family; Hill family; Lawrence family; Stevens family; Townley family; Genealogy; Maryland -- Genealogy; New Jersey -- Genealogy; New York (State) -- Genealogy; Virginia -- Genealogy; Genealogists; Lawyers